Trabalho livre e ordem burguesa: (Rio Grande do Sul - 1870-1900) - Pesavento, Sandra Jatahy (Revista de História, 1989)
This article studies from a specific marxist perspective (Francisco de Oliveira, Meillassoux, etc.) an aspect of capitalist development in Brazil which was the late mercantilization of land after abolition. The abolition of the slave trade and the land decree of 1850 are suggested parameters for the elites'project for a gradual transition to free labor. Different aspects of land policy are described as tending towards keeping ex-slaves as workers away from access to small properties and contributing towards concentration of land ownership as part of the interest of dominant classes in maintaining a cheap labor force. After abolition, prices in land went up while Italian immigrants were imported to keep the monopoly of land and of the means of subsistence in the hands of the rural coffee elite.